The Influence of Raw Material Inventory Control on Production Targets at Wery Bakery in Gunungsitoli City: - Lahagu, Feberlius; Zebua, Serniati; Harefa, Idarni; Zebua, Emanuel (ProBisnis : Jurnal Manajemen, 2024)
Inventory management is a planned approach to determine what to order, when to order and how many orders and how much stock so that the costs associated with purchasing and storing are optimal without disrupting production and Production targets are company limits on a production output based on planning- plans set by the company. The purpose of this research is to determine the control of raw material inventory at Wery Bakery in Gunungsitoli City, to determine the production target at Wery Bakery in Gunungsitoli City, to find out whether there is an influence of raw material inventory control on production targets at Wery Bakery in Gunungsitoli City and to find out how much The big influence of controlling raw material supplies on production targets at Wery Bakery in Gunungsitoli City. The total sample is 13 people, Quantitative research type. The results of the study that: 1). All questionnaires used in data collection in the field were declared feasible and valid to use, where rxy>rtable, 2). The value based on the calculation of the determinant coefficient, the correlation of variable X (processing of raw material supplies) to variable Y (production target) was 42, 25%. 3). From the results of simple linear regression calculations obtained the equation Y = 13.880 + 0.637 (X). 4). t test with dk = 13 at a significant level = 0.05 where tcount> t table is 2.837> 2.201 So it is proven that the accepted hypothesis is Ha, namely there is an influence of raw material inventory control on production targets at Wery Bakery in Gunungsitoli City and Ho is rejected.